Performance of crusher machine for crushing coconut coir into cocopeat and coco fibre - Anugrah, R.A. (Universitas Mataram, 2022)
The abundant resources of coconut coir in Indonesia, especially a tiny village in Kulon Progo district, namely Kadigunung, hadn't been used before this research. It was thrown away and mostly just burned by the villagers. Even though it can be used to become natural organic fertilizer for agriculture, most of the population members are making a living as farmers. But there is a problem when processing to make the fertilizer, and it is the use of conventional manner to crush the coconut coir into cocopeat and coco fibre. So they needed appropriate technology and crusher machines. It is a gasoline-powered crushing device with 5.5 hp and 2000 rpm. It has 21 moving and 12 fixed blades. The research data were obtained by digital tachometer and sound level meter measurements. Other data were also measured by formula calculation. The results of this research involved the data of fuel consumption, the machine's capacity, depreciation of raw coconut coir, noise level, linear v-belt velocity, and rpm of the blade shaft. They were 1.8 L, 0.05 kg, 99.3 dB, 2π m/s, and 330 rpm, respectively. So it can be inferred that the crushing machine is a good performance.